Analisis Pengaruh Corporate Social Responsibility Terhadap Return Saham Dengan ROE Sebagai Variabel Moderating Pada Indeks LQ-45. - Nofimbi Fitriani; Ali Sadikin; Amalia Wahyuni (Al-KALAM : JURNAL KOMUNIKASI, BISNIS DAN MANAJEMEN, 2021)
This research type is a causality with the aim of analyzing the effect of Corporate Social Responsibility on stock returns with profitability as a moderating variable on the LQ-45 Stock Index during the 2013-2017 period. The research population is all companies listed in the LQ-45 Index on the Indonesia Stock Exchange during 2013-2017. The sampling using purposive sampling method with a total sample of 23 companies. Data of this research is quantitative type with data analysis techniques consisting of descriptive analysis, testing classic assumptions, moderating regression analysis, and testing hypotheses. The results showed that there was a significant positive effect on testing the effect of Corporate Social Responsibility on Stock Returns. While the high or low profitability (Return on Equity) is considered unable to moderate the influence of Corporate Social Responsibility on Stock Returns because of the large expenditure incurred for Corporate Social Responsibility can have a negative impact on business operations that will reduce the level of profitability obtained by the investor.